PENETAPAN KADAR FLAVONOID EKSTRAK DAUN MATOA (Pometia pinnata) MENGGUNAKAN METODE SPEKTROFOTOMETRI UV-VIS - Ginting, Suventi Syafrina; Sianipar, Masria phetheresia; ., Sulasmi; Charissa, Jilli; Mardiana, Nova (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2025)
One of the medicinal plants found in Indonesia is the matoa plant (Pometia pinnata). This matoa plant is a typical plant from Papua and has spread widely in Sumatra, Java, Sulawesi, Maluku and the island of Sumbawa. This matoa plant is known to contain flavonoid compounds which are proven to have high pharmacological effects as antioxidants, antibacterial and antifungal agents. Flavonoids are compounds that can be found in green plants that have bioactive effects such as antiviral and anti-inflammatory. The purpose of this study was to determine the levels of flavonoids in the leaf extract of matoa (pometia pinnata) using the uv-vis spectrophotometric method. The method used in this research is experimental, including sampling, processing phytochemical screening samples and making matoa leaf extract. Matoa leaf simplicia was extracted using maceration method using 96% ethanol. In this study, validation of analytical methods with parameters, namely linearity, accuracy, precision, LOD & LOQ uses uv-vis spectrophotometry with a wavelength of 435nm. The results obtained from the correlation coefficient (r) = 0.9977, the results obtained from the accuracy test were 99.92% with requirements (90%-110%), The results from the precision test obtained RSD/Kv of 0.366 % and the LOD value of 2.6802 ppm and LOQ of 8.9341 ppm. The results of determining the flavonoid content of matoa leaf extract (Pometia pinnata) were obtained with a value of 67.0207 mgQE/g Extract.